Bortezomib is significantly beneficial for de novo pediatric AML patients with low phosphorylation of the NF‐κB subunit RelA. Issue 2 (17th November 2021) - van Dijk, Anneke D.; Hoff, Fieke W.; Qiu, Yihua; Gerbing, Robert B.; Gamis, Alan S.; Aplenc, Richard; Kolb, E. Anders; Alonzo, Todd A.; Meshinchi, Soheil; Jenkins, Gaye N.; de Bont, Eveline S. J. M.; Kornblau, Steven M.; et al.
Abstract: Purpose: The addition of the proteasome inhibitor (PI) bortezomib to standard chemotherapy (ADE: cytarabine [Ara‐C], daunorubicin, and etoposide) did not improve overall outcome of pediatric AML patients in the Children's Oncology Group AAML1031 phase 3 randomized clinical trial (AAML1031) . Bortezomib prevents protein degradation, including RelA via the intracellular NF‐kB pathway. In this study, we hypothesized that subgroups of pediatric AML patients benefitting from standard therapy plus bortezomib (ADEB) could be identified based on pre‐treatment RelA expression and phosphorylation status. Experimental design: RelA‐total and phosphorylation at serine 536 (RelA‐pSer 536 ) were measured in 483 patient samples using reverse phase protein array technology. Results: In ADEB‐treated patients, low‐RelA‐pSer 536 was favorably prognostic when compared to high‐RelA‐pSer 536 (3‐yr overall survival (OS): 81% vs. 68%, p  = 0.032; relapse risk (RR): 30% vs. 49%, p = 0.004). Among low‐RelA‐pSer 536 patients, RR significantly decreased with ADEB compared to ADE (RR: 30% vs. 44%, p = 0.035). Correlation between RelA‐pSer 536 and 295 other assayed proteins identified a strong correlation with HSF1‐pSer 326, another protein previously identified as modifying ADEB response. The combination of low‐RelA‐pSer 536 and low‐HSF1‐pSer 326 was a significant predictor of ADEB response (3‐yr OS: 86% vs. 67%, p = 0.013). Conclusion and clinical relevance: Bortezomib may improve clinical outcome in a subgroup of AML patients identified by low‐RelA‐pSer 536 and low‐HSF1‐pSer 326 .